Examining how marginalized stakeholders successfully redress their issues: A social networks approach. Issue 1 (8th June 2015) - Shivarajan, Sridevi; DuBois, Thomas; Srinivasan, Aravind
Abstract : Purpose: – Can marginalized stakeholders whose issues with the firm are unaddressed because of their resource and legitimacy constraints (low salience) increase their salience by capitalizing on certain inherent properties of their stakeholder environment? The purpose of this paper is to examine this question using a real life case of the Coca-Cola controversy in Kerala, India, where a group of local aboriginals succeeded against all odds in shutting down a Coca-Cola plant which was allegedly polluting their water resources. The analysis of the longitudinal data collected in this case supported the hypotheses that the ability of marginalized stakeholders to increase their salience by influencing other stakeholders depends both on the attributes of other stakeholders (favorable, unfavorable and indifferent), and the triadic relationships among them. The triadic relationships among stakeholders show a tendency toward balance, and become particularly relevant when the marginalized stakeholder's issues are perceived to have low legitimacy due to their normative nature (which makes them difficult to be translated into economic terms). The findings offer important insights to both marginalized stakeholders and firms, on proactively managing their stakeholder environments. Design/methodology/approach: – The authors use a single case: the controversy surrounding Coca-Cola in Kerala, India, and conduct a longitudinal study examining both qualitative and quantitative data. Findings: – The findings indicate that marginalized stakeholders can capitalize on certain inherent properties of their stakeholder networks and increase their salience to influence the focal firm. Specifically, the authors find that stakeholder salience is a function of both the dyadic relationships between stakeholders, and the triadic relationships among them. These triadic relationships tend to a state of balance over time. The authors also find that when the stakeholder issue is normative in nature the triadic relationships are more important in increasing stakeholder salience. Originality/value: – The authors conduct an original case study research, with primary qualitative data collected by the authors. The authors also develop a quantitative model to examine this data to arrive at the findings. Therefore the authors contribute both theoretically and empirically to stakeholder salience literature.